Geography alive! : - Hart, Diane (Teachers' Curriculum Institute, 2011)
Created in partnership with scholars from the National Council for Geographic Education, Geography Alive! Regions and People creatively challenges students to use the tools of geography to view, analyze, and understand the world around them.